2013
DOI: 10.1186/1752-153x-7-47
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative activity of hexane extract from Tunisian Cistus libanotis, Cistus monspeliensis and Cistus villosus

Abstract: BackgroundAs a part of our investigation on Tunisian medicinal plants, we have carried out a phytochemical investigation of the hexane extracts from leaves of Cistus libanotis, C. villosus and C. monspeliensis, evualuating also their possible antiproliferative activity in vitro.ResultsThe major compounds of hexane extracts were identified and quantified by GC-MS. The composition of the three species, although belonging to the same genus, is completely different. The antiproliferative activity was evaluated aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 28 publications
3
30
0
2
Order By: Relevance
“…Analysis of essential oil composition of C. monspeliensis grown in Tunisia led to the identification of accountable amounts of oxygenated sesquiterpenes and sesquiterpene hydrocarbons (Loizzo et al, 2013). Another study conducted with plants at the same site detected a large variety of sesquiterpenes but at low concentrations (Jemia et al, 2013). Several sesquiterpenes were also isolated from C. monspeliensis plants naturally growing in areas of France and Greece (Robles and Garzino, 2000; Angelopoulou et al, 2001a, 2002; Rivoal et al, 2010).…”
Section: Chemical Analysesmentioning
confidence: 97%
See 2 more Smart Citations
“…Analysis of essential oil composition of C. monspeliensis grown in Tunisia led to the identification of accountable amounts of oxygenated sesquiterpenes and sesquiterpene hydrocarbons (Loizzo et al, 2013). Another study conducted with plants at the same site detected a large variety of sesquiterpenes but at low concentrations (Jemia et al, 2013). Several sesquiterpenes were also isolated from C. monspeliensis plants naturally growing in areas of France and Greece (Robles and Garzino, 2000; Angelopoulou et al, 2001a, 2002; Rivoal et al, 2010).…”
Section: Chemical Analysesmentioning
confidence: 97%
“…The monoterpene phenol carvacrol was a major constituent of Tunisian C. monspeliensis leaves and essential oils, while other polyphenolic compounds such as diisobutyl ester (phthalic acid) and benzyl benzoate were also strongly represented (Jemia et al, 2013; Loizzo et al, 2013). Moreover, carvacrol and α-terpineol were the only monoterpene compounds isolated from leaf essential oil of C. monspeliensis plants found in Crete (Greece) (Angelopoulou et al, 2001a, 2002), while several phenolic acid derivatives were identified in plants grown in Spain (Barrajón-Catalán et al, 2011).…”
Section: Chemical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…The Cistaceae family (consisting of eight genera and 175 species) includes the genus Cistus, which comprises about 20 shrub species found broadly throughout the entire Mediterranean region (COMANDINI et al, 2006, TOMAS-MENOR et al, 2013 In Mediterranean folk medicine, Cistus species have been used as general remedies (BARRAJÓN-CATALÁN et al, 2010) and for their antiinflammatory (DEMETZOS et al, 2001), antiulcerogenic, wound healing, anti-microbial (DEMETZOS et al,1999, antifungal (BAYOUB et al, 2010), antiviral, anti-tumor (DIMAS et al, 2000, cytotoxic (BEN JEMIA et al, 2013) and antinociceptive (BARRAJÓN-CATALÁN et al, 2010) properties. For example, tea prepared from C. salvifolius L. herb (AL-KHALIL, 1995) has traditionally been used for the treatment of gout (AL-KHALIL, 1995) and ulcers (YESILADA et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Inne badania wskazują na antykancerogenne działanie tej rośliny. Na polskim rynku jest dostępny cięty, suszony czystek, ale także gotowe mieszanki herbat z jego zawartością [2,5,6].…”
unclassified